Urban poverty, inequality and industry in Nigeria - Mustapha, Alhaji Bukar; Said, Rusmawati; Sidique, Shaufique Fahmi (Emerald Group Publishing, 2015)
Purpose – The purpose of this paper is to examine the relationship between industrial sector growth, inequalities and urban poverty reduction